Synthetic Applications of Amino Acid Derived Aldehydes in Asymmetric Hydroxylation Reactions Using Nitrosobenzene - Jain, Vipin Kumar; Dhillon, Sudeep; Kinger, Mayank (SynOpen, 2025)
This review highlights the proline-catalyzed asymmetric α-hydroxylation of aldehydes derived from amino acids. This reaction provides a robust method for introducing a hydroxyl group at the α-position of the aldehyde with high stereocontrol. The stereochemical outcome of the hydroxylation is primarily governed by the chiral environment of the proline catalyst and is further influenced by the pre-existing chiral center within the substrate. Post-hydroxylation, the aldehyde intermediates can be readily transformed into alcohols or olefins, depending on the synthetic requirements. We explore the utility of amino acid derived aldehydes, such as those obtained from l-glutamic acid, phenylalanine, proline, and l-aspartic acid, in the context of asymmetric synthesis. The scope of this methodology extends to the efficient construction of various natural products and bioactive compounds, highlighting its significance in modern organic synthesis.1 Introduction2 Mechanistic Overview of the Proline-Catalyzed Asymmetric α-Hydroxylation of Aldehydes3 Review of the Proline-Catalyzed Asymmetric α-Hydroxylation of Aldehydes4 Current Overview and Future Prospective5 Conclusion
Keywords: catalysis; asymmetric; proline; amino acid; hydroxylation; aldehyde; stereoisomer